The Existence of Long-Run PPP: A Comparison between Developed and Developing Countries - Sulistiadi Dono Iskandar (Institute for Economic and Social Research, 2016)
McNown & Wallace (1989) argued that PPP will tend to holds in less developed countries due to the domination of nominal factors in the economy. In this study we try to investigate the existence of long-run PPP in eight countries consisting four developed and developing countries. Here we show that there is a strong evidence that long-run PPP holds for Germany, United Kingdom, and Chile. Furthermore, the additional tests also show that symmetry and proportionality conditions seem to hold in the three economies. As for other five economies, long-run PPP seems to be absence. Although one step general Error Correction Model and Johansen-Juselius cointegration procedure generates conflicting result, the result of both technique do not show a tendency for PPP to hold in developing countries thus rejecting argument proposed by McNown and Wallace. AbstrakMcNown & Wallace (1989) mengemukakan argumen bahwa PPP akan cenderung berlaku di negara-negara yang belum maju disebabkan adanya dominasi faktor nominal dalam perekonomian. Dalam penelitian ini kami mencoba untuk menyelidiki keberadaan dari long-run PPP di delapan negara yang terdiri dari empat negara maju dan berkembang. Hasil estimasi menunjukkan adanya bukti kuat bahwa long-run PPP berlaku pada Jerman, Inggris, dan Cile. Hasil, tes lanjutan juga menunjukkan bahwa kondisi simetri dan proporsionalitas nampak bertahan di tiga negara tersebut. Sedangkan untuk lima negara lainnya, long-run PPP tidak nampak keberadaannya. Meskipun hasil pada one step Error Correction Model (ECM) dan Johansen-Juselius cointegration procedure menghasilkan hasil yang bertentangan, namun hasil dari kedua metode tersebut konsisten tidak menunjukkan kecenderungan akan eksistensi PPP di negara berkembang.Kata kunci: Purchasing Power Parity; Tes Kointegrasi; Negara Berkembang; Negara MajuJEL classifications: F31; F4